Web database - Gunnit S Khurana (Waite group, 1996)
Getting started; Dissecting a job listing system; Building a database with microsoft access; Building microsoft access queries; Designing advanced queries; Elements of the world wide web; Creating HTML forms; Windows common gateway interface...